Evaluating the procurement systems within the department of infrastructure development for better service delivery - Zvomunya, Memory (My University, 2018)
South Africa is currently faced with the challenge of reducing the huge backlog of infrastructure delivery to communities that were previously disadvantaged. Specifically, the Government needs to deliver school infrastructure to accommodate the rapidly growing student population particularly in areas that have experienced high levels of urban migration. It is generally agreed that there is need to step up the quality of planning, costing and project management, to speed up the delivery process of schools in line with the schools calendar. This research report critically assesses the characteristics and application of procurement systems currently being utilised by Gauteng Department of Infrastructure Development (GDID) for the delivery of school buildings. GDID utilises three procurement systems; the traditional, the integrated and the management-oriented procurement systems, providing an opportunity to compare the performance of each system within a single organisational context. A descriptive survey was conducted for school projects with the same prototype design executed within GDID, to identify the external and internal factors that are complimentary or detrimental to the effective implementation of the different procurement systems. Data was collected and the content analysed. The literature research confirms that different procurement systems have an effect on the total project delivery time, assuming all other variables remain constant. The integrated procurement system was found to be the most suitable procurement system for schools service delivery projects, from initiation to close out, for GDID, given the tight time frameworks. However, due regard should be given to extensive communication with all stakeholders to obtain their buy-in and approvals.
A research report submitted to the Faculty of Engineering and Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Building. Johannesburg, 2018
Keywords: Sustainable architecture; Sustainable buildings--Design and construction